2013
DOI: 10.17509/bs_jpbsp.v13i2.287
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the English Syllabus of Room Division Department Related to the Needs of the Hotel Industries: A Case Study at One Tourism Institute in Bandung

Abstract: Investigating the English Syllabus of Room Division Department Related to the Needs of the Hotel Industries: A Case Study at One Tourism Institute in Bandun g. This study investigates what English syllabus needed by the first year students of R oom Division Department in one tourism institute in Bandung. In this study, three hot els, 35 fifth semester students of Room Division Department and one English lecturer were involved. The purpose of this study is to find out the Room Division students' n eeds in learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…The teachers in their study reported that logistical problems such as lack of facilities and equipment and crowded classrooms kept them from focusing on oral communication skills, which, in turn, led to designing summative assessment that included paragraph writing, multiple-choice vocabulary and grammar questions, and a translation section. Similar inauthentic test tasks because of logistics-related issues were also apparent in several other studies (e.g., Handayaningrum & Setiawan, 2013;Trinder, 2013;Zahedpisheh et al, 2017).…”
Section: Task Designsupporting
confidence: 78%
See 2 more Smart Citations
“…The teachers in their study reported that logistical problems such as lack of facilities and equipment and crowded classrooms kept them from focusing on oral communication skills, which, in turn, led to designing summative assessment that included paragraph writing, multiple-choice vocabulary and grammar questions, and a translation section. Similar inauthentic test tasks because of logistics-related issues were also apparent in several other studies (e.g., Handayaningrum & Setiawan, 2013;Trinder, 2013;Zahedpisheh et al, 2017).…”
Section: Task Designsupporting
confidence: 78%
“…Due to the dazzling speed of globalization in the workforce and the dominant use of English as a de facto working language, there has been a significant amount of demand for workplace-specific English language courses (Marra, 2013). However, there is a discrepancy between what is expected in the workplace and classroom practices in ESP courses (Abdel- Ghany & Abdellatif, 2012;Handayaningrum & Setiawan, 2013;Trinder, 2013;Zahedpisheh et al, 2017). One way to promote changes in teaching is to change how we assess students in these ESP courses.…”
Section: English For Specific Purpose Assessmentmentioning
confidence: 99%
See 1 more Smart Citation